Antibiograms in five pipetting steps: precise dilution assays in sub-microliter volumes with a conventional pipette. Issue 5 (25th January 2016) - Derzsi, Ladislav; Kaminski, Tomasz S.; Garstecki, Piotr
Abstract : A standalone microfluidic chip allows to carry out an antibiotic susceptibility test with an automatic pipette and with minimum manual labour. Abstract : We demonstrate a standalone microfluidic chip that allows us to carry out commonly executed antibiotic susceptibility assays in an array of nanoliter droplets. We eliminated the need for automation in performing an exemplary complicated liquid handling assay on a chip. Operations on droplets are hard-wired into the microfluidic chip. The liquid handling protocol can be executed with a simple and commonly available source of flow such as an automatic manual pipette. The system passively prepares a series of dilutions of a chemical compound and mixes them with portions of the sample. The precision of metering, merging, mixing, and splitting of discrete portions of liquid samples is rooted in the passive capillary action in microfluidic traps and not in the precision of dosing with a pipette. We show an exemplary use of the device in the determination of the minimum inhibitory concentration (MIC) of ampicillin against E. coli ATCC 25922.